2005
DOI: 10.1590/s0103-64402005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of denture surface glazing on denture plaque formation

Abstract: This study evaluated, in vivo, the efficacy of a denture glazing material (Palaseal) in modifying plaque colonization of dentures. Ten subjects were selected and received maxillary temporary partial removable dentures, with complete acrylic palatal coverage. The right half of the fitting surface of the denture bases were glazed with Palaseal, whereas the other half was not glazed. One month after insertion, two fragments of the resin base of all dentures were removed (one from the glazed side and another from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 16 publications
8
34
0
14
Order By: Relevance
“…Furthermore, to improve surface quality, Mantikos et al 25 propose the application of a layer of glaze, claiming that in provisional restorations, this procedure is indicated to reduce bacterial attachment. However, Sesma et al 26 demonstrated that glaze applied on definitive surfaces did not prevent bacterial attachment, although it aided its removal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to improve surface quality, Mantikos et al 25 propose the application of a layer of glaze, claiming that in provisional restorations, this procedure is indicated to reduce bacterial attachment. However, Sesma et al 26 demonstrated that glaze applied on definitive surfaces did not prevent bacterial attachment, although it aided its removal.…”
Section: Discussionmentioning
confidence: 99%
“…Palaseal surface sealant agent selected for this study is a light-cured sealer that adhere to all denture materials and has high resistance to solvents 23) . Sesma et al 24) reported that sealant agent coupling (Palaseal) may improve the physical properties of dentures with smoother surface, decrease plaque adhesion and bacterial colonization, which results in good oral hygiene. Consistent with this results, no significant difference was found between the initial surface roughness values (R a0) of all tested denture base materials in present study, which had been coated with Palaseal sealant agent before.…”
Section: Discussionmentioning
confidence: 99%
“…Sesma ve ark. 19 cila materyallerinin protez yüzeyindeki plak formasyonuna etkinliğini değerlendirdikleri in vivo çalıĢmalarında, Palaseal uygulanan protezlerin taramalı elektron mikroskop görüntüle-rinin, Palaseal uygulanmayanlara göre daha düzgün olduğunu bildirmiĢlerdir. Hareketli protezlerin hastaya teslimi sırasında veya sonrasında yapılan aĢındırmalara bağlı olarak açığa çıkan pürüzlü yüzeylerin düzenlenmesi amacıyla da cila pastaları veya silikon cila kitleri kullanılmak-tadır.…”
Section: Discussionunclassified